Endoscopic injection sclerotherapy in the treatment of bleeding oesophageal varices in patients with portal hypertension due to alcohol-induced cirrhosis : an assessment of acute control of bleeding, prevention of recurrent bleeding and prognostic factors predicting early variceal rebleeding and death - Krige, J E J (Department of Surgery, 2016)
The ideal treatment of portal hypertension and bleeding varices should be universally effective, safe, easy to administer and inexpensive. Currently no such treatment exists and the surgeon or physician is obliged to select the most appropriate intervention from a menu of currently available therapeutic options, none of which is ideal or applicable to all patients. The rational treatment of oesophageal varices depends on a clear understanding of the risks of rebleeding and the response to each specific intervention. The selection of the correct and appropriate intervention is critical and requires a comprehensive understanding of the relative efficacy and safety of each treatment compared to other competing options. In addition, the chosen intervention requires detailed knowledge of the criteria underpinning the correct selection of patients for treatment in order to maximize the therapeutic benefits of the appropriate choice while minimising the side effects of the treatment. The optimal management of bleeding oesophageal varices therefore requires a full appreciation of portal, gastric and oesophageal venous collateral anatomy, the pathogenesis and haemodynamic consequences of variceal bleeding and the utility of each available therapy at specific stages in the natural history of portal hypertension (Henderson 1998).